1987
DOI: 10.1002/star.19870390105
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Maize Hulls with Water in a Flow Reactor

Abstract: Maize hull hemicelluloses can be extracted almost quantitatively by simple water treatment ("prehydrolysis") in a flow reactor at 165-180°C. Severe decomposition of pentosans is thus avoided. Concomitant solubilized starch can be separated from hemicelluloses by degradation with glucoamylase as was shown on an analytical scale. The obtained xylan (yields around 25%) is partly depolymerized and about 50% of original arabinose present in the side chains are split of. Nevertheless the isolated p r o d g , which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Apparently, the pentosans are protected during the pretreatment of biomass while in the form of oligomers. Köll et al also found that the majority of hemicellulose in corn fiber solubilized with hot liquid water (165−180 °C for 60 min) was in the polymeric form (70%), although the pentosan recovery was not reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, the pentosans are protected during the pretreatment of biomass while in the form of oligomers. Köll et al also found that the majority of hemicellulose in corn fiber solubilized with hot liquid water (165−180 °C for 60 min) was in the polymeric form (70%), although the pentosan recovery was not reported.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, acetic acid is formed from the partial deacetylation of hemicellulose, and this acid may catalyze the hydrolysis reactions. The hemicellulose is also depolymerized. , For example, an initial, mild (180 °C, 1 h) water extraction (“prehydrolysis”) has long been used to selectively remove most of the hemicellulose from pine before chemical pulping. , Complete removal of the hemicellulose from hardwoods and herbaceous materials, without significant degradation, was achieved by Mok and Antal using higher temperatures (200−230 °C) for 15 min and less. Lignin is also partially depolymerized and solubilized during treatments with hot water. Complete delignification is not possible using hot liquid water alone, in part because of recondensation of soluble components originating from lignin.…”
Section: Introductionmentioning
confidence: 99%